Pengaruh Kompetensi, Kompensasi, dan Latar Belakang terhadap Kinerja Guru - Tatan Zaenal Mutakin (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2013)
This research aimed to determine the effect of competencies, compensation, and background on the performance of elementary school mathematics teacher at DKI Jakarta, Banten and West Java. Research method used was a survey with a sample of 203 respondents. Sampling technique using multi-stage random sampling. Collecting data using questionnaires that have been validated by a team of experts. Data analysis using path analysis. The results of the data analysis results: 1) In total competence of teachers has an impact on 42.55% increase in teacher performance, 2) Background of teachers in total have an impact of 2.35% on improved teacher performance, 3) Together teacher competencies and background of 44.9% effect on the performance of lementary school math teacher.